Past and future impact of the winter North Atlantic Oscillation in the Caspian Sea catchment area - Sri D. Nandini‐Weiss; Matthias Prange; Klaus Arpe; Ute Merkel; Michael Schulz (International Journal of Climatology, 2020)
The Caspian Sea level (CSL) has undergone variations of more than 3 m during the past century with important implications for the life of coastal people, economy and the ecosystem. The origin of these variations as well as future changes in the Caspian water budget are still a matter of debate. Here, the major modes of North Atlantic winter climate variability and atmospheric teleconnections that have a potential effect on the hydroclimate of the Caspian catchment region are examined. The skill of the Community Earth System Model (CESM1.2.2) regarding the simulation of the modern climatology in the Caspian region and the major North Atlantic modes are analysed using different atmospheric grid resolutions and setups of the atmospheric component, the Community Atmosphere Model (CAM4 and CAM5). CESM1.2.2 with CAM5 atmosphere physics and 1° atmospheric grid resolution shows reasonable skill in simulating the regional Caspian basin climatology and the winter North Atlantic Oscillation (NAO). Using this model version, a weakly positive ( r = .2) statistically significant ( p r = .5, p